Editorial Comment: Can Deans be Taught Management Principles? - Vance, Stanley (Academy of Management Journal, 1967)
The article discusses deans of schools of business administration, and what qualifications and qualities they are likely to have in order to be hired. The article asks how to measure a dean's effectiveness and motivate optimal performance. The article applauds the reinstatement of a seminar for new deans at the American Association of Collegiate Schools of Business annual meeting. The author provides information about deans such as the most common degrees held, academic interest area, and books authored.